Associations of genetic variants in/near body mass index‐associated genes with type 2 diabetes: a systematic meta‐analysis. (13th March 2014) - Xi, Bo; Takeuchi, Fumihiko; Meirhaeghe, Aline; Kato, Norihiro; Chambers, John C.; Morris, Andrew P.; Cho, Yoon Shin; Zhang, Weihua; Mohlke, Karen L.; Kooner, Jaspal S.; Shu, Xiao Ou; Pan, Hongwei; et al.
Summary Objective Genome‐wide association studies have identified many obesity/body mass index (BMI)‐associated loci in Europeans and East Asians. Since then, a large number of studies have investigated the role of BMI‐associated loci in the development of type 2 diabetes (T2D). However, the results have been inconsistent. The objective of this study was to investigate the associations of eleven obesity/BMI loci with T2D risk and explore how BMI influences this risk. Methods We retrieved published literature from PubMed and Embase. The pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated using fixed‐ or random‐effect models. Results In the meta‐analysis of 42 studies for 11 obesity/BMI‐associated loci, we observed a statistically significant association of the FTO rs9939609 polymorphism (66 425 T2D cases/239 689 normoglycaemic subjects; P = 1·00 × 10−41) and six other variants with T2D risk (17 915 T2D cases/27 531 normoglycaemic individuals: n = 40 629–130 001; all P < 0·001 for SH2B1 rs7498665, FAIM2 rs7138803, TMEM18 rs7561317, GNPDA2 rs10938397, BDNF rs925946 and NEGR1 rs2568958). After adjustment for BMI, the association remained statistically significant for four of the seven variants (all P < 0·05 for FTO rs9939609, SH2B1 rs7498665, FAIM2 rs7138803, GNPDA2 rs10938397). Subgroup analysis by ethnicity demonstrated similar results. Conclusions This meta‐analysis indicates that several BMI‐associated variants are significantly associated with T2D risk. Some variants increase the T2D risk independent of obesity, while others mediate this risk through obesity.